PARCELAMENTO DE NITROGÊNIO EM CULTIVARES DE ALGODÃO PORTADORAS DO CARÁTER CLUSTER - OLIVEIRA, Izadora Araujo,; SILVA, Kelly Gabriela Pereira da,; SILVA, Ricardo Leonel,; SILVA, Rafael Alves,; BRAMBILLA, Henry Vinicíus Ribeiro,; ZOZ, Tiago, (ANAIS DO ENIC, 2022)
-